2012
DOI: 10.2308/isys-10254
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of E-Prescriptions and Automated Medication-Management Systems in Hospitals: An Extension of the Technology Acceptance Model

Abstract: The serious repercussions of heath care errors on patient safety have led hospitals to deploy corrective information technologies. Hospitals are moving away from traditional paper-based systems and focusing on designing new methods that reduce errors, using information technology to catalyze the reengineering process.This paper analyzes the intention of health care personnel (physicians and nurses) to use e-prescriptions and automated medication-management systems (EPAMMS), identifying influencing factors. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 78 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…TAM was proposed by Davis (1989) to study the role of human behavior attributes in the acceptance of an information system. TAM is an adaptation of a psychological theory, Escobar-Rodriguez and Romero-Alonso (2013) 118 Medical staff E-health system TAM Glegg et al (2013) 42 Medical staff E-health tool DTPB Guo et al (2013) 204 Public E-health system TAM Hendrikx et al (2013) 68 Patients E-health system TAM Huang (2013) 369 Public E-health tool TAM (continued ) Kuo et al (2013) 665 Medical staff E-health tool TAM Liu et al (2013) 50 Patients E-health tool TAM Martínez-Caro et al (2013) 256 Patients E-health system TAM Monthuy- Blanc et al (2013) 205 Medical staff E-health tool TAM Noblin et al (2013) 560 Patients E-health tool TAM Nuq and Aubert (2013) 329 Medical staff E-health system TAM Sun et al (2013) 204 Public E-health system TAM, TPB Tsai et al (2013) 101 Public E-health tool TAM Aldosari (2012) 89 Medical staff E-health system TAM Bhagya Lakshmi and Rajaram (2012) 465 Medical staff E-health system TAM Chen and Hsiao (2012) 81 Medical staff E-health system TAM Dünnebeil et al (2012) 117 Medical staff E-health system TAM Escobar- Rodríguez et al (2012) 209 Medical staff E-health tool TAM Hung and Jen (2012) 170 Public E-health system TAM 224 Medical staff E-health tool DTPB Ketikidis et al (2012) 133 Medical staff E-health system TAM Kim and Park (2012) 728 Public E-health system TAM 449 Patients E-health system TAM Kowalczyk (2012) 110 Medical staff E-health tool TAM2 Lu et al (2012) 277 Medical staff E-health system TAM Maass and Varshney (2012) 51 Public E-health system TAM, TPB Wirtz et al (2012) 502 Medical Staff E-health tool TAM Xue et al (2012) 700 Public E-health tool TAM Cudmore et al (2011) 192 Public E-health system TAM Dyball et al (2011) 48 Medical staff E-health system TAM Egea and González (2011) 254 Medical staff ...…”
Section: Tam and Related Theoriesmentioning
confidence: 99%
“…TAM was proposed by Davis (1989) to study the role of human behavior attributes in the acceptance of an information system. TAM is an adaptation of a psychological theory, Escobar-Rodriguez and Romero-Alonso (2013) 118 Medical staff E-health system TAM Glegg et al (2013) 42 Medical staff E-health tool DTPB Guo et al (2013) 204 Public E-health system TAM Hendrikx et al (2013) 68 Patients E-health system TAM Huang (2013) 369 Public E-health tool TAM (continued ) Kuo et al (2013) 665 Medical staff E-health tool TAM Liu et al (2013) 50 Patients E-health tool TAM Martínez-Caro et al (2013) 256 Patients E-health system TAM Monthuy- Blanc et al (2013) 205 Medical staff E-health tool TAM Noblin et al (2013) 560 Patients E-health tool TAM Nuq and Aubert (2013) 329 Medical staff E-health system TAM Sun et al (2013) 204 Public E-health system TAM, TPB Tsai et al (2013) 101 Public E-health tool TAM Aldosari (2012) 89 Medical staff E-health system TAM Bhagya Lakshmi and Rajaram (2012) 465 Medical staff E-health system TAM Chen and Hsiao (2012) 81 Medical staff E-health system TAM Dünnebeil et al (2012) 117 Medical staff E-health system TAM Escobar- Rodríguez et al (2012) 209 Medical staff E-health tool TAM Hung and Jen (2012) 170 Public E-health system TAM 224 Medical staff E-health tool DTPB Ketikidis et al (2012) 133 Medical staff E-health system TAM Kim and Park (2012) 728 Public E-health system TAM 449 Patients E-health system TAM Kowalczyk (2012) 110 Medical staff E-health tool TAM2 Lu et al (2012) 277 Medical staff E-health system TAM Maass and Varshney (2012) 51 Public E-health system TAM, TPB Wirtz et al (2012) 502 Medical Staff E-health tool TAM Xue et al (2012) 700 Public E-health tool TAM Cudmore et al (2011) 192 Public E-health system TAM Dyball et al (2011) 48 Medical staff E-health system TAM Egea and González (2011) 254 Medical staff ...…”
Section: Tam and Related Theoriesmentioning
confidence: 99%
“…Today, in line with the notion that “access to the right information at the right time is a crucial ingredient of modern healthcare” (Nicholas et al , 2001, p. 157), there are enormous applications of ICT used in the Health Sector which have the potential to secure and improve appropriately the management of healthcare information, access to health services, and the quality of care with less costs. This is what Escobar‐Rodríguez et al (2012, p. 78) highlight: “IT plays a fundamental role in improving the quality of health care service while increasing its efficiency”. On the other hand, among the most notable organisations which have experienced such a change affected by technological developments we can name libraries.…”
Section: Introductionmentioning
confidence: 83%
“…The serious implications of their actions for patients and the considerable responsibility they assume could mean that intention to use a technology might depend on factors related to improving PSQ and not on usability issues. 20 Furthermore, Gururajan showed that the ease-of-use factor was not strongly significant in the health care domain when determining wireless technology adoption. The health care environment is complex, sensitive, and time critical.…”
Section: Discussionmentioning
confidence: 99%
“…19 Most studies have focused on health professionals' behavioral intention to use health care technology. 20,21 Holden and Karsh highlighted the necessity of contextualizing the TAM model for health care settings and suggested that this could be done by differentiating between performance benefits accruing at the personal and group levels, focusing on health care outcomes, and allowing for different sources of social influences. 12 For example, Sun et al extended IT usage models to include the role of IT's perceived work compat-ibility in shaping users' IT usage intention, usage, and performance in a work setting.…”
Section: Conceptual Frameworkmentioning
confidence: 99%